1999
DOI: 10.1093/milmed/164.6.389
|View full text |Cite
|
Sign up to set email alerts
|

The Tripler LE3AN Program: A Two-Year Follow-Up Report

Abstract: This paper provides a review of 2-year follow-up data on the Tripler Army Medical Center LE3AN Program. The LE3AN Program (emphasizing healthy Lifestyles, reasonable Exercise, realistic Expectations, Emotions, and Attitudes, and Nutrition) provides active duty service members a treatment strategy that involves a reasonable low-intensity exercise regimen, behavior modification, intensive nutritional counseling healthy meal planing, relapse prevention strategies, cognitive coping strategies, and healthy lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Where comparison is possible [34,35,54], a reduction in reported body fat (Cohen's d = 0.42-0.66) as opposed to body weight (d = 0.14-0.38) or BMI (d = 0.03-0.53) was observed to be more significant. Several of the interventions [26][27][28][29][30]34] could be defined as successful as they produced reductions in body weight beyond that required by the US Institute of Medicine [35] ( 5% of initial body weight). Whilst the most successful (>10% weight loss) interventions [29,30] approach advocated by previous reviews [17,36,37] and classifies correlates as demographic and biological; psychological, cognitive and emotional; dealing with behavioural attributes and skills; social and cultural; dealing with physical environment; or dealing with PA characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Where comparison is possible [34,35,54], a reduction in reported body fat (Cohen's d = 0.42-0.66) as opposed to body weight (d = 0.14-0.38) or BMI (d = 0.03-0.53) was observed to be more significant. Several of the interventions [26][27][28][29][30]34] could be defined as successful as they produced reductions in body weight beyond that required by the US Institute of Medicine [35] ( 5% of initial body weight). Whilst the most successful (>10% weight loss) interventions [29,30] approach advocated by previous reviews [17,36,37] and classifies correlates as demographic and biological; psychological, cognitive and emotional; dealing with behavioural attributes and skills; social and cultural; dealing with physical environment; or dealing with PA characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of dietary modification and diet education was another central topic of most of the interventions and is reflective of recent literature [19,44]. Two studies [24,27] reported the dietary modification applied (male 1,500-2,000 kcal/day , female 1,400-1,600 kcal/day), and these values are broadly in keeping with civilian recommendations [45]. Whilst both studies were successful in reducing body weight, the 'multi-component' nature of the interventions precludes comment as to the efficacy of the individual component.…”
Section: Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Web site usage because of the anonymous study design, whereas previous studies were able to identify participants. In addition, previous studies utilized group-and/or clinic-based behavioral treatment approaches, 10,14 and exclusively enrolled soldiers exceeding the STW, which resulted in a sample seeking weight loss treatment. By design, our population-based intervention was made available to all Army Reserve soldiers, irrespective of their weight status or intentions concerning weight management.…”
Section: Discussionmentioning
confidence: 99%